Manfaat Informasi Akuntansi untuk Memprediksi Risiko Investasi Saham Berdasarkan Pendekatan Decision Usefulness - Puspitaningtyas, Zarah (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
This study is to explain the usefulness of accounting information to predict the risk of stock investment based on the decision usefulness approach, technically shown through the effect of variable accounting on risk of stock investment. Based on analysis of 13 companies over a period of five years (2001-2005) by using multiple linear regression, the model shows that the current ratio significantly influence the risk of stock investment. However, signs of regression coefficients are not consistent with the predictions of the study. The results indicate that the current ratio has positive influence on the risk of stock investment. F test shows that the regression model with the current ratio as independent variables significantly influence the risk of stock investment. Meanwhile, the regression model with independent variables of current ratio, debt equity ratio, total assets turnover, return on investment, sales growth, and price earnings ratio do not significantly influence the risk of stock investment. The findings suggest that accounting information has relatively little ability to explain variations in risk of stock investment. The validation of regression models shows no difference between the real investment risk and investment risk prediction, meaning that accounting information is useful for predicting the risk of stock investment.